2006
DOI: 10.1007/s00332-005-0736-z
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of Heteroclinic Orbits for Some Analytic Unfoldings of the Hopf-Zero Singularity

Abstract: Summary. In this paper we study the exponentially small splitting of a heteroclinic connection in a one-parameter family of analytic vector fields in R 3 . This family arises from the conservative analytic unfoldings of the so-called Hopf zero singularity (central singularity). The family under consideration can be seen as a small perturbation of an integrable vector field having a heteroclinic orbit between two critical points along the z axis. We prove that, generically, when the whole family is considered, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 34 publications
2
47
0
Order By: Relevance
“…Let us observe that, taking ε = δ p+2 we recover the result given in [4] for p > −2 when ε is small and we deal with the case corresponding to a generic unfolding taking ε = 1.…”
Section: Baldomá and T M Searasupporting
confidence: 57%
See 2 more Smart Citations
“…Let us observe that, taking ε = δ p+2 we recover the result given in [4] for p > −2 when ε is small and we deal with the case corresponding to a generic unfolding taking ε = 1.…”
Section: Baldomá and T M Searasupporting
confidence: 57%
“…Then the system becomes: , p = −2, and f, g, h = O( (δx, δy, δz, δ) 3 ) are analytic functions in B(r 0 ). In [4] the authors studied this system in the perturbative case p > −2 and they gave a rigorous proof of the breakdown of a heteroclinic orbit (located at x = y = 0) that exists if we consider only the terms coming from the normal form, that is, the case f = g = h = 0. The proof consisted in validating that the first order perturbation theory, that in this case was explicitly given by a Melnikov function, provided the correct prediction even if the Melnikov function (and the corresponding distance between the invariant manifolds) was exponentially small with respect to the parameter δ.…”
Section: Baldomá and T M Searamentioning
confidence: 99%
See 1 more Smart Citation
“…This theory of zero-Hopf bifurcation has been analyzed by Guckenheimer, Han, Holmes, Kuznetsov, Marsden and Scheurle in [8,9,13,14,17]. In particular they shown that some complicated invariant sets of the unfolding could bifurcate from the isolated zero-Hopf equilibrium under convenient conditions, showing that in some cases the zero-Hopf bifurcation could imply a local birth of "chaos", see for instance the articles [2,3,4,7,17] of Baldomá and Seara, Broer and Vegter, Champneys and Kirk, Scheurle and Marsden. Note that the differential system (1) only depends on one parameter so it cannot exhibit a complete unfolding of a zero-Hopf bifurcation. For studying the zero-Hopf bifurcation of system (1) we shall use the averaging theory in a similar way at it was used in [5] by Castellanos, Llibre and Quilantán.…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%
“…In particular it is shown that some complicated invariant sets of the unfolding could bifurcate from the isolated zero-Hopf equilibrium under some conditions. Hence in some cases the zero-Hopf bifurcation could imply a local birth of "chaos" see for instance the articles [22][23][24][25][26] of Baldomá and Seara, Broer and Vegter, Champneys and Kirk, Scheurle and Marsden.…”
mentioning
confidence: 99%